Automated preforming and manufacturing of hollow thermoplastic composites - Liu, Chongsheng (Nanyang Technological University, 2021)
Bladder Assisted Resin Transfer Moulding process (B-RTM) is one of the technologies which is widely used in the manufacturing of hollow structural composite materials. The tubular composite manufactured in this project uses epoxy resin and a new acrylic thermoplastic material Elium® as the matrix, hybrid fiber (composed of woven carbon fiber and Innegra, polypropylene fabric) and pure Innegra as the reinforcement. Manufacturing process optimization is an important means to improve the quality of the final product. By designing and improving the process, the fiber performance quality and efficiency are improved, and then the best pressure parameters are obtained through repeated trials and tests, including bladder pressure, injection pressure and consolidation pressure. Through the above improvement and optimization process, composite hollow parts with high fiber fraction, low porosity and uniform thickness can be realized. After completing the optimization process, four different kinds of composite tubular structures with hybrid fiber and pure Innegra as the reinforcement, Elium® and epoxy resin as the matrix were manufactured. There were subjected to flexure, vibration and impact tests. The resulting tubular composite was also subjected to low-speed impact tests at multiple energy levels to obtain the relationship between time, load and energy, and combined with high-speed cameras and microscopes for more accurate failure analysis. Compared with Carbon Innegra Epoxy Composite (CIEP), the peak load of Carbon Innegra Elium® Composite (CIEL) configuration parts have been reduced by about 10%, while Innegra Elium® Composite (INEL) compared to Innegra Epoxy (INEP) had increased by a maximum of 41.4%. In terms of energy absorption, CIEL had a maximum increase of 49.31% compared to CIEP, and INEL and INEP showed similar energy absorption, which were related to the different deformation and failure types during impact. A three-point bending test method was adopted, a suitable support span was selected and a saddle was used to prevent stress concentration. Experiments were done on the performance difference between CIEL and CIEP, INEL and INEP in terms of flexure, i.e., comparing their bending stress (max) and Modulus (E). It was noticed that CIEL was lower than CIEP by 35.6% and 18.9% in the above two configuration parameters, while INEL was more than 17.8% in Modulus (E) compared to INEP. At the same time, videos recorded during the flexure were used to compare the deformation that occurred in the experiment and determined the failure mechanism with the help of microscopic observation. In the modal analysis test, CIEL's structural damping results showed that compared with CIEP and INEP tubular configurations, CIEL had a similar structural damping rate, while INEL's damping rate was 43.48% higher. The presence viscoelasticity and matrix ductility in case of thermoplastic Elium® was the main factor causing the difference. At the same time, the thickness of the tube and the fiber volume fraction also had different degrees of influence on it. Current project used a new type of composite material production process to compare and studied the difference in characteristics between the new type of thermoplastic material and the traditional thermosetting epoxy resin. At the same time, the new thermoplastic matrix material Elium® also possessed the characteristics of energy saving and environmental protection, which would provide a feasible alternative to the traditionally used epoxy resin composite system. This kind of developed tubular structure can be widely used in sports, automobile, aerospace and other industries, and has great potential.